Phosphorylation of Ribosomal Protein S3 and Antiapoptotic TRAF2 Protein Mediates Radioresistance in Non-small Cell Lung Cancer Cells - Yang, Hee Jung (American Society for Biochemistry and Molecular Biology, 2013)
Radioresistance is considered as a main factor restricting efficacy of radiotherapy. However, the exact molecular mechanism of radioresistance has not been explained yet. In this study, to elucidate radioresistance mechanism in lung cancer, we compared radiation responses in two types of non-small cell lung cancer (NSCLC) cells with different radiosensitivity and identified key molecules conferring radioresistance. In radioresistant NSCLC cells, ionizing radiation (IR) led to casein kinase 2α (CK2α)- and PKC-mediated phosphorylation of rpS3 and TRAF2, respectively, which induced dissociation of rpS3-TRAF2 complex and NF-κB activation, resulting in significant up-regulation of prosurvival genes (cIAP1, cIAP2, and survivin). Also, dissociated phospho-rpS3 translocated into nucleus and bound with NF-κB complex (p65 and p50), contributing to p65 DNA binding property and specificity. However, in radiosensitive NSCLC cells, IR-mediated rpS3 phosphorylation was not detected due to the absence of CK2α overexpression. Consequently, IR-induced rpS3-TRAF2 complex dissociation, NF-κB activation, and prosurvival gene expression were not presented. Taken together, our findings revealed a novel radioresistance mechanism through functional orchestration of rpS3, TRAF2, and NF-κB in NSCLC cells. Moreover, we provided the first evidence for the function of rpS3 as a new TRAF2-binding protein and demonstrated that phosphorylation of both rpS3 and TRAF2 is a key control point of radioresistance in NSCLC cells. These results suggest that regulation of rpS3 and TRAF2 in combination with radiotherapy could have high pharmacological therapeutic potency for radioresistance of NSCLC.